Calcitonin and exocrine pancreatic secretion in man: inhibition of enzymes stimulated by CCK-pancreozymin, caerulein, or calcium—no response to vagal stimulation. Issue 8 (August 1977) - Hotz, J.; Goebell, H.; Ziegler, R.
Abstract : The effect of calcitonin on human pancreatic secretion was studied under various conditions of stimulation. During administration of both secretin plus cholecystokinin-pancreozymin (CCK-PZ) or secretin plus caerulein, enzyme secretion was promptly reduced by an infusion of calcitonin of more than 50%. In contrast, vagally stimulated enzyme secretion induced by insulin-hypoglycaemia or carbamyl-choline was not altered against a background infusion of calcitonin in comparison with control experiments. Calcium-induced enzyme secretion was abolished by additional calcitonin infusion which also prevented an increase in serum calcium. On the other hand, additional high grade calcium infusion did not modify the inhibitory action of calcitonin on enzyme output stimulated by secretin and CCK-PZ. Secretion of fluids and bicarbonate remained unaffected by calcitonin in all experimental conditions, whereas the outputs of calcium and magnesium paralleled generally the changes in enzymes. It is suggested that calcitonin interferes with hormonemediated stimulation of the acinar cells without influencing cholinergic mechanisms. The inhibitory action of calcitonin on enzyme secretion does not appear to be mediated by a depletion of extracellular calcium in the pancreatic tissue by calcitonin.